Physiological and transcriptomic analysis reveal the crucial factors in heat stress response of red raspberry ‘Polka’ seedlings - Guo, Juanjuan; Zhang, Ruiyu; Cheng, Siqi; Fu, Ziqian; Jia, Peng; Luan, Haoan; Zhang, Xuemei; Qi, Guohui; Guo, Suping (Frontiers in Plant Science, 2023)
With global climate warming, recurring extreme heat and high temperatures irreversibly damages plants. Raspberries, known for its nutritional and medicinal value, are in high demand worldwide. Thus, it is important to study how high-temperature stress (HTS) affects raspberries. The physiological, biochemical responses, and molecular genetic mechanisms of raspberry leaves to different HTS treatments: mild high temperature at 35°C (HT35), severe high temperature at 40°C (HT40), and the control at room temperature of 25°C (CK). The effects of HTS on photosynthesis, antioxidant protective enzyme systems, osmoregulation, and RNA-seq in raspberry leaves were studied. The physiological results suggested that leaves in both the 35°C and 40°C treatments showed maximum relative conductivity at 4 d of stress, increasing by 28.54% and 43.36%, respectively, compared to CK. Throughout the stress period (0-4 d), malondialdehyde (MDA) and soluble protein contents of raspberry leaves increased under HT35 and HT40 treatments, while soluble sugar content first decreased and then increased. Catalase (CAT) activity increased, superoxide dismutase (SOD) activity first increased and then decreased, and peroxidase (POD) activity gradually decreased. Photosynthetic and fluorescence responses of raspberry leaves showed the most severe impairment after 4 d of stress. Transcriptomics results revealed significant alterations in 42 HSP family genes, two SOD-related differentially expressed genes (DEGs), 25 POD-related DEGs, three CAT-related DEGs, 38 photosynthesis-related DEGs under HTS. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis showed that these DEGs were mainly enriched in photosynthesis-antenna proteins, pentose and glucuronide interconversion, phenylpropane biosynthesis, and indole alkaloid biosynthesis. HTS induced excessive ROS accumulation in raspberry leaves, causing oxidative damage in plant cells and subsequently reducing photosynthesis in raspberry leaves. This reduction in photosynthesis, in turn, affects photosynthetic carbon fixation and starch and sucrose metabolism, which, combined with phenol propane biosynthesis, mitigates the HTS-induced damage.